The work of breathing does not limit the maximal exercise performance of humans at sea-level - Ansley, L.; Petersen, D.; Thomas, A.; Noakes, T. D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
could be a major contributing factor to the termination of exercise. Indeed there have been a number of studies that have reported the benefits of inspiratory muscle training on exercise tolerance (Volianitis et al, 2001). Similarly, it has been found that breathing a mixture of helium and oxygen is characterised by higher maximal minute ventilation and oxygen consumption values and results in enhanced exercise performance (Wilson et al, 1980). However, attempting to elucidate the extent of the role of respiratory fatigue in limiting exercise performance, through the manipulation of internal breathing resistance, is confounded by the changes in external breathing resistance effected by the artificial gas delivery systems. Therefore the observations from the early studies are more likely to be explained by the increased effort of breathing during the control trial and the subsequent reduction in the breathing resistance through the external respiratory tubing when the helium mixture was breathed. Methods To evaluate the separate and combined effects of O2 delivery and respiratory muscle work on incremental maximal exercise performance, we exercised 8 highly trained cyclists in an atmospherically-sealed chamber in which inspired O2 concentrations were elevated (FIO2 = 0.30) and helium (He) was substituted for nitrogen in the ambient air in order to reduce the work of breathing during exercise. This system ensured that external inspiratory and expiratory resistance was minimised and identical in all experimental conditions and approximated conditions present during normal exercise. The elevated O2 concentration during both conditions also ensured that any effect of increased O2 availability was minimised in the helium trial. A t-test was performed on the data with significance accepted at p<0.05. Results Substituting helium for nitrogen had no beneficial effect on maximal work output (451 ± 58 vs. 454 ± 56 W) (Fig 1a) or VO2max (5.0 ± 0.6 vs. 4.9 ± 0.7 L.min-1) (Fig 1b) and although submaximum VE was attenuated with helium, VEmax was unchanged (157 ± 24 L.min-1 vs. 163 ± 22 L.min-1) (Fig 1c). Discussion/Conclusion Careful individual analysis of the data identified an unaccountable decrease of 28 L.min-1 in the maximal ventilation of subject 3 during the heliox trial and exclusion of their data revealed a significant increase in VEmax in the heliox condition from 156 ± 26 L.min-1 to 167 ± 20 L.min-1 (p<0.02). However, this was not accompanied by a concomitant difference in either maximal VO2 or workload. Therefore, we conclude that since exercise was terminated at the same peak work rate (± 3 W) in both hyperoxic and heliox conditions, which implies a common limiting factor, the work of breathing does not limit maximal exercise.